2015
DOI: 10.3109/07420528.2015.1104327
|View full text |Cite
|
Sign up to set email alerts
|

Daily rhythms of lipid metabolic gene expression in zebra fish liver: Response to light/dark and feeding cycles

Abstract: Despite numerous studies about fish nutrition and lipid metabolism, very little is known about the daily rhythm expression of lipogenesis and lipolysis genes. This research aimed to investigate the existence of daily rhythm expressions of the genes involved in lipid metabolism and their synchronization to different light/dark (LD) and feeding cycles in zebra fish liver. For this purpose, three groups of zebra fish were submitted to a 12:12 h LD cycle. A single daily meal was provided to each group at various t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 74 publications
2
26
1
Order By: Relevance
“…Human core clock genes identified from hair follicle cells follow the same trend as the Zebrafish data (Fig 3B) [51]. This difference may be due the diurnal/nocturnal activity pattern between these animals [52,53] although clock genes were shown to not always follow this pattern between nocturnal and diurnal species of fish [54,55]. The Zebrafish dawn cluster that had a phase of ZT1.6 in Fig 2B has now a phase of ZT13.6 in mouse while the dusk cluster phased at ZT12.7 is now expressed at ZT21.8 (Fig 3B).…”
Section: Resultsmentioning
confidence: 77%
“…Human core clock genes identified from hair follicle cells follow the same trend as the Zebrafish data (Fig 3B) [51]. This difference may be due the diurnal/nocturnal activity pattern between these animals [52,53] although clock genes were shown to not always follow this pattern between nocturnal and diurnal species of fish [54,55]. The Zebrafish dawn cluster that had a phase of ZT1.6 in Fig 2B has now a phase of ZT13.6 in mouse while the dusk cluster phased at ZT12.7 is now expressed at ZT21.8 (Fig 3B).…”
Section: Resultsmentioning
confidence: 77%
“…Under constant light conditions, leptin-a expression was rhythmic in goldfish that were fed at 10:00, but was not rhythmic in those that were fed at 22:00 or randomly, suggesting that feeding time alone cannot induce daily leptin rhythms in this species (Tinoco et al 2014). These hepatic leptin-a rhythms also did not shift according to the feeding time in zebrafish under an LD cycle, indicating that light is probably the dominant synchroniser (Paredes et al 2015). In addition, these daily leptin rhythms may also be regulated by rhythmic endogenous factors (hormones and foodderived metabolites), as described in mammals (Challet 2015, Kumar et al 2015.…”
Section: Leptinmentioning
confidence: 72%
“…However, as stated previously, hepatic leptin expression rhythms are not always linked to clock genes daily rhythms in the liver of goldfish (Tinoco et al 2014). Furthermore, although feeding time drives clock genes oscillations in the sea bream liver (Vera et al 2013), it does not control the rhythms of enzymes that are involved in lipid metabolism (Paredes et al 2014); and in zebrafish, lipid metabolism is linked to the LD cycle and independent of feeding time (Paredes et al 2015). Thus, the physiological functions of peripheral oscillators in fishes remain unclear.…”
Section: Communication Among Oscillators: Hormones As Temporal Internmentioning
confidence: 91%
See 1 more Smart Citation
“…() indicated that alkaline protease activity in midgut of O. niloticus showed a daily rhythm, and both the achrophase appeared at the beginning of the dark phase in both 1,100 and 2,300 groups. Paredes, López‐Olmeda, Martínez and Sánchez‐Vázquez () revealed that most genes about lipid metabolic gene expression in liver of zebra fish displayed a significant daily rhythm with an acrophase of expression in the dark phase, which showed a strong synchronization to the L/D cycle, feeding time barely influenced daily expression rhythms. In the view of these studied, the DEGs in intestine of P. vachellii may dominantly result in L/D cycle.…”
Section: Discussionmentioning
confidence: 99%